2023
DOI: 10.1093/rheumatology/kead141
|View full text |Cite
|
Sign up to set email alerts
|

Unpublished clinical trials of common rheumatic diseases

Abstract: Objectives Randomized controlled trials (RCTs) provide high-quality evidence for treatment efficacy, but many RCTs remain unpublished. The objective of this study was to describe the proportion of unpublished RCTs in 5 rheumatic diseases and to identify factors associated with publication. Methods Registered RCTs for 5 rheumatic diseases (systemic lupus erythematosus, vasculitis, spondyloarthritis, Sjögren’s syndrome, and pso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Preparation and submission of the manuscript, peer‐review process, multiple resubmissions, quality of the reporting, and study methodology all contribute to the time needed for a paper to be published ( 3 ). Additionally, it has been shown that publication and time from study completion to publication is often associated with the tendency from investigators, study sponsors, or journal editors to favor a more rapid dissemination of results that are statistically significant ( 4 , 5 ) or have a relatively large treatment effect (time‐lag publication bias) ( 6 ). This practice undermines the validity of the overall knowledge on a given topic skewing evidence toward positive findings and is therefore as deleterious as nonpublication of study results.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation and submission of the manuscript, peer‐review process, multiple resubmissions, quality of the reporting, and study methodology all contribute to the time needed for a paper to be published ( 3 ). Additionally, it has been shown that publication and time from study completion to publication is often associated with the tendency from investigators, study sponsors, or journal editors to favor a more rapid dissemination of results that are statistically significant ( 4 , 5 ) or have a relatively large treatment effect (time‐lag publication bias) ( 6 ). This practice undermines the validity of the overall knowledge on a given topic skewing evidence toward positive findings and is therefore as deleterious as nonpublication of study results.…”
Section: Introductionmentioning
confidence: 99%